Multimedia-Based Learning Application for the History of Islam's Entry into Indonesia and the Stories of the Sunans - Ada Udi Firmansyah; Median Satria; Aura Maharani Darmawan; Febri Sugandi; Aditya Susanti (International Journal Software Engineering and Computer Science (IJSECS), 2026)
History education in primary schools often relies on textbook-based instruction, which may limit students’ interest and participation in the learning process. This study aimed to develop an interactive multimedia learning application for teaching the history of the arrival of Islam in Indonesia and the Walisongo. The development process involved field observations, interviews with educational experts, and a literature review to collect and validate the historical learning materials. The validated materials were implemented in an offline multimedia application using graphic design and animation software. The application included an interactive interface, Indonesian-language narration, background audio, and multiple-choice quizzes to support students’ learning activities and evaluation. The developed application was evaluated through expert validation, pretest-posttest assessment, and student responses. The results showed that the application was suitable for use as a learning medium and received positive responses from students. The pretest-posttest results also indicated an improvement in students’ learning outcomes after using the application. The study indicates that interactive multimedia can serve as an alternative learning medium for supporting history learning, particularly on the history of Islam in Indonesia and the Walisongo.